Tetraflagellochloris mauritanica gen. et sp. nov. (Chlorophyceae), a New Flagellated Alga From the Mauritanian Desert: Morphology, Ultrastructure, and Phylogenetic Framing. Issue 1 (25th October 2012) - Barsanti, Laura; Frassanito, Anna Maria; Passarelli, Vincenzo; Evangelista, Valtere; Etebari, Maryam; Paccagnini, Eugenio; Lupetti, Pietro; Lenzi, Paola; Verni, Franco; Gualtieri, Paolo
<x xml:space="preserve">Abstract</x> Morphological, ultrastructural, and molecular‐sequence data were used to assess the phylogenetic position of a tetraflagellate green alga isolated from soil samples of a saline dry basin near F'derick, Mauritania. This alga can grow as individual cells or form non‐coenobial colonies of up to 12 individuals. It has a parietal chloroplast with an embedded pyrenoid covered by a starch sheath and traversed by single parallel thylakoids, and an eyespot located in a parietal position opposite to the flagellar insertion. Lipid vacuoles are present in the cytoplasm. Microspectroscopy indicated the presence of chlorophylls a and b, with lutein as the major carotenoid in the chloroplast, while the eyespot spectrum has a shape typical of green‐algal eyespots. The cell has four flagella, two of them long and two considerably shorter. Sequence data from the 18S rRNA gene and ITS2 were obtained and compared with published sequences for green algae. Results from morphological and ultrastructural examinations and sequence analysis support the placement of this alga in the Chlorophyceae, as Tetraflagellochloris mauritanica L. Barsanti et A. Barsanti, gen. et sp. nov.